The potential of paleoecology for functional forest restoration planning: lessons from Late Holocene Italian pollen records. (4th May 2018) - Piovesan, Gianluca; Mercuri, Anna Maria; Mensing, Scott A.
Abstract: We describe forest landscape transformations during the last two millennia in the Italian peninsula by analyzing local (Rieti basin – Lago Lungo) and regional (RF93-30 Adriatic Sea) sediment cores. We identify a dynamic forest ecosystem through paleoecologic reconstruction and consider potential interventions for effective restoration of the most ancient, least disturbed forest ecosystem. The most degraded ecosystems in consequence of human activities were hygrophilous (wet) and mesic forests. In the Rieti Basin, degraded forest ecosystems on mountain slopes are undergoing some degree of forest succession and have less need of restoration. However, management plans for biodiversity, ecosystem services and resources conservation are needed to achieve more sustainable development. In Rieti, the paleoecological investigation revealed a dramatic decrease of deciduous wet and mesic tree taxa through time due to human landscape transformation. The starting point for restoration of a Mediterranean forest ecosystem that preserves natural biodiversity and associated ecosystem services requires recreating some portion of the floodplain wetland ecological niche. Once floodplain forest ecological niche has been recreated, the original ecosystem composed of Alnus, Fraxinus excelsior, Tilia spp., Carpinus betulus and Acer spp., all species which today are rare, should be planted on the basis of microsite characteristics and tree autoecology.